Engineering Students’ Generic Skills After Industrial Training: Employers’ Perception - Ghazalan, Mohd Shahzuan; Ab Halim, Fazlinda; Hamidon, Nur Izeanty; Ahmad Hariri, Tun Ily Ayuni; Sallehuddin, Shamim Asilah; Bahrol, Khadijah; Zakaria, Normah; Roddin, Rohayu (Journal of Technical Education and Training, 2019)
This study aims to examine the employers’ perception on the generic skills of the MTU engineering students after their industrial training. The related generic skills in this study are problem-solving skills, leadership skills, communication skills, management skills, entrepreneurial skills, critical thinking skills, decision making skills, teamwork skills and interpersonal skill. The sample of this study consists of 144 employers from EEE (Electrical and Electronic Engineering) field industries that has been chosen from whole Malaysia using random sampling. The design of the study uses quantitative survey approach specifically descriptive analysis where data analysis is done in the form of mean, frequencies and percentages. (The results show that employers’ perceptions on the level for students’ leadership skills is at a moderate low of 2.77.On the other hand, the students’ communication skills is at a moderate low level of 2.83, management skills at a moderate high level of 3.34, interpersonal skills at a moderate high level of 3.37, problem-solving skills at a moderate high level of 3.70, critical thinking skills at a moderate high level of 3.47, decision-making skills at moderate high of 4.13 and teamwork skills at moderate high of 3.64 and entrepreneurial skills at moderate low of 2.59. ) Referring to the findings that it can help the university to re-evaluate the industry training curriculum to improve the quality of the student’s generic skills. Therefore, it is hoped that these research findings can be used by related authorities (Ministry Higher Education and Industry) to improve the students’ overall generic skills and consequently produce quality graduates not only in technical skills but also in generic skills. This findings will be used as a guideline in the improvement of the industry training curriculum by looking at the weakest level of generic skills based on the employer’s perception.